2014
DOI: 10.1186/1471-2431-14-20
|View full text |Cite
|
Sign up to set email alerts
|

Are parents' knowledge and practice regarding immunization related to pediatrics’ immunization compliance? a mixed method study

Abstract: BackgroundImmunization rate is one of the best public health outcome and service indicators of the last 100 years. Parental decisions regarding immunization are very important to improve immunization rate. The aim of this study was to evaluate the correlation between parental knowledge-practices (KP) and children's immunization completeness.MethodsA mixed method has been utilized in this study: a retrospective cohort study was used to evaluate immunization completeness; a prospective cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 34 publications
4
33
0
4
Order By: Relevance
“…Qutaiba B et al showed inadequate knowledge regarding immunization in 48.5% of the study population group. 19 A study done in Mangalore demonstrated that 30% of mothers had poor knowledge while 44% had average knowledge regarding immunization. 20 In the present study, 63.3% mothers stated that vaccination is beneficial to the baby.…”
Section: Discussionmentioning
confidence: 99%
“…Qutaiba B et al showed inadequate knowledge regarding immunization in 48.5% of the study population group. 19 A study done in Mangalore demonstrated that 30% of mothers had poor knowledge while 44% had average knowledge regarding immunization. 20 In the present study, 63.3% mothers stated that vaccination is beneficial to the baby.…”
Section: Discussionmentioning
confidence: 99%
“…Educating mothers whose children are at risk of not completing the immunization schedule is an important strategy to improve immunization coverage [ 25 ]. An educational programme about the importance of immunization is needed, especially for parents with a lower educational level, in order to improve the immunization rate [ 26 29 ]. To our knowledge, no study in Malaysia has assessed the impact of educational programming for improving Malaysian parents’ knowledge of their children’s immunization.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge is also related to sources of information provided by maternity clinics, the media, literature, and the internet which cover vaccination benefits and the risks of vaccine-preventable diseases. [6] Many studies have also shown that parents" knowledge regarding child immunization varies according to level of exposure, level of education, interaction with the family physician and other medical staff. [7], [8], [9], [ 10] There is presently a dearth of literature on the current level of awareness and knowledge of mothers in rural Ondo State, therefore, the current study is aimed at assessing the knowledge of mothers in Akure North…”
Section: Introductionmentioning
confidence: 99%